INDUSTRY 4.0 CIVIL ENGINEER JOB SKILLS REQUIRED BY EMPLOYERS IN MALAYSIA (Jurnal Kemanusiaan, 2019)
We are in the commencment of Fourth Industrial Revolution that will transform the way of humans live and work style. Changes in the style of work in the 21st century happen to improve the country's economy. The changing nature of work and employment in the fourth industrial revolution force people to find the needs for well-developed skills for future job market. Rapid changes in the world of work require university providers to strengthen their role in producing highly skilled human capital to cater the industrial demands. Therefore, this study attempts to investigate civil engineering job skills and abilities that required for new generation civil engineers in Malaysia. This paper aimed to review the lists of skills needed by the employers for civil engineers in Malaysia. The findings presented for a necessary frameworks of job skills to civil engineering students to prepare their abilities for the future job demand.